Biomacromolecule immobilization: grafting of fish-scale collagen peptides onto aminolyzed P(3HB-co-4HB) scaffolds as a potential wound dressing. (6th October 2016) - Vigneswari, S; Murugaiyah, V; Kaur, G; Abdul Khalil, H P S; Amirul, A A
Abstract: Polyhydroxyalkanoate (PHA) is a microbial polymer that has been at the forefront of many attempts at tissue engineering. However, the surface of poly(3-hydroxybutyrate- co -4-hydroxybutyrate) (P(3HB- co -4HB)) is hydrophobic with few recognition sites for cell attachment. Various concentrations of fish-scale collagen peptides (FSCPs) were incorporated into P(3HB- co -4HB) copolymer by aminolysis. Later, FSCPs were introduced onto the aminolyzed P(3HB- co -4HB) scaffolds. Introduction of the FSCP groups was verified using Fourier transform infrared spectroscopy and the ninhydrin method. The effect of the incorporation of FSCPs on hydrophilicity was investigated using the water contact angle. As the concentration of FSCPs increased, the water contact angle decreased. In vitro study demonstrated that P(3HB- co -4HB)/FSCP scaffolds provided better cell attachment and growth of L929 mouse fibroblast cells and better cell proliferation. In vivo study showed that P(3HB- co -4HB)/1.5 wt% FSCPs had a significant effect on wound contractions, with the highest percentage of wound closure (61%) in 7 d.